PERANAN INFORMASI DALAM PEMBANGUNAN - Saefuddin, Ahmad Muflih (Jurnal Bestari, 1993)
Development program in every developed and developing country cannot be separated from information as one of the main pillars. The great achivements of developed countries, usually, based on and identified by many achievements of information technology. To get a better life in the hopefull future, Indonesia as ine of the developing countries, must be aware of global information.